Modeling and experimental validation of a Wf/W-fabrication by chemical vapor deposition and infiltration. (September 2021) - Raumann, L.; Coenen, J.W.; Riesch, J.; Mao, Y.; Schwalenberg, D.; Wegener, T.; Gietl, H.; Höschen, T.; Linsmeier, Ch.; Guillon, O.
Abstract: Tungsten (W) has a unique combination of excellent thermal properties, low sputter yield, low hydrogen retention, and acceptable activation. Therefore, W is presently the main candidate for the first wall material in future fusion devices. However, its intrinsic brittleness and its further embrittlement during operation bears the risk of a sudden and catastrophic component failure. As a countermeasure, tungsten fiber-reinforced tungsten (W f /W) with extrinsic toughening is being developed. A possible synthesis route is chemical vapor deposition (CVD) using heated W fabrics as substrate. The challenge is that the growing CVD-W can isolate domains from precursor access leading to strength-reducing pores. To deepen the process understanding and to optimize the CVD parameters, models were developed with COMSOL Multiphysics and validated experimentally. W deposition rate equations as function of the temperature and the partial pressures of the precursors H 2 and W F 6 were experimentally validated in previous work. In the present article, these equations are applied to obtain partial pressures within the CVD reactor. The results are taken as input for transient simulations in the microscale, in which W coatings, growing onto multiple adjacent W fibers, were simulated via mesh deformation and remeshing. The surface-to-surface contact of the W coatings and the corresponding potential pore formation were simulated by implementing sophisticated deposition rate stop conditions. Within the measuring uncertainties of ≃ ± 1%, the models are validated successfully by experimental comparison regarding the deposition rate, pore structure, and relative densities ranging from 0.6 to 0.9. Highlights: CVD/CVI of W on multiple adjacent fibers was modeled using COMSOL Multiphysics. Coating growth simulated by transient FEM mesh deformation and remeshing. Gas-to-surface and surface-to-surface interactions were considered. Partial pressure inputs obtained from a stationary macroscaled reactor simulation. Experimental validation via coating thickness, pore structure and relative density.